Perseroan Perorangan Pada Usaha Mikro dan Kecil: Kedudukan dan Tanggung Jawab Organ Perseroan - Yustisia Utami, Putu Devi; Sudiarawan, Kadek Agus (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021)DO - 10.24843/JMHU.2021.v10.i04.p08, 2021)
The purpose of this article was to determine the position of company organs and to analyze the authority and responsibility of company organs in Individual Limited Liability Company. This study used a normative juridical method with a statutory and concept approach. The study indicated that the position of the company's organs in Individual Limited Liability Company is different from the Limited Liability Company organs. The organs of Limited Liability Company consist of the General Meeting Shareholders (GMS), Board of Directors and the Board of Commissioners, while the organs of the Individual Limited Liability Company consist of Shareholders as well as Directors and doesn’t have Board of Commissioners. The authority and responsibility of the Individual Limited Liability Company organs can be seen in the provisions of article 109 number (5) of the Job Creation Law which includes articles 153 letter d and 153 letter j. Individual Limited Liability Company in Indonesia adhere to the one tier system, but there are differences between the one tier system in Indonesia and the Anglo Saxon countries. The company's organs in Anglo Saxon countries still consist of the GMS, Directors and Commissioners who can hold concurrent positions, whereas in Individual Limited Liability Company in Indonesia, shareholders only hold concurrent positions. as the Board of Directors and eliminate the organs of the Board of Commissioners. Individual Company Organs in PP No. 8/2021 is not in accordance with the provisions of the company organs in the above regulations, namely the Job Creation Law and the Company Law. Penulisan artikel ini bertujuan untuk mengetahui kedudukan organ perseroan pada perseroan perorangan serta menganalisis wewenang dan tanggung jawab organ perseroan perorangan. Metode hukum normatif dengan pendekatan perundang-undangan dan pendekatan konsep dipergunakan dalam penelitian ini. Hasil menunjukkan bahwa kedudukan organ perseroan pada perseroan perorangan berbeda dengan organ PT pada umumnya. Organ PT terdiri dari RUPS, Direksi dan Dewan Komisaris, sedangkan organ perseroan perorangan terdiri dari Pemegang Saham sekaligus Direktur namun tidak memiliki organ Dewan Komisaris. Wewenang dan tanggung jawab organ perseroan perorangan dapat dilihat pada ketentuan pasal 109 angka (5) UU Cipta Kerja yang menyisipkan pasal 153 huruf d dan 153 huruf j. Perseroan perorangan di Indonesia menganut one tier system, namun terdapat perbedaan mengenai one tier system yang dianut oleh Indonesia dengan yang dianut oleh negara Anglo Saxon. Pada negara Anglo Saxon organ perseroan tetap terdiri dari RUPS, Direksi dan Komisaris yang dapat dirangkap jabatan, sedangkan pada perseroan perorangan di Indonesia pemegang saham hanya merangkap jabatan sebagai Direksi dan tidak ada organ Dewan Komisaris. Organ perseroan perorangan pada PP No. 8/2021 tidak sesuai dengan ketentuan organ perseroan pada peraturan diatasnya yakni UU Cipta Kerja dan UUPT.